Determination of idebenone in plasma by HPLC/MS - Hu Pei; Jiang Ji; Xie Hong-Hong (Acta Pharmacologica Sinica, 2016)
"AIM: To develop a sensitive method for the analysis of idebenone [Ide, 6-(10-hydroxydecyl)-2,3-dimethoxy-5-methyl-p-benzoquinone] in human plasma. METHODS: The concentrations in plasma were determined by a high performance liquid chromatography-mass spectrometry coupled with an atmosphere pressure chemical impact ion source method (LC/MS-APCI). RESULTS: The chromatograms indicated a good separation of the analytes and there was no interference by other compounds. The coefficients of determination of the calibration curves were above 0.999. The calibration range was 20-600 micrograms.L-1. Peak plasma idebenone concentration (Cmax) of (316 +/- 85) micrograms.L-1 was achieved within (96 +/- 34) min (Tpeak) after an oral dose of 30 mg. Lower limit of quantitation of the method for Ide determination was 20 micrograms.L-1. CONCLUSION: The advantages of using LC/MS-APCI technique include better sensitivity, higher selectivity, and less time consumption, compared with HPLC method."